Design guidelines for Arabic mobile learning application based on cognitive theory of multimedia learning - Al-Rikabi, Mohammed Abbas Neamah (2016)
Arabic Language has an exceptional position in Islam. As the language of al-Quran, the needs to learn and understand it amongst Muslims is of paramount importance. In countries where their native language is not Arabic, it needs to be introduced to children at their early age such as in primary schools. With the advent of mobile technology, various kinds of multimedia tools have been developed for the purpose of learning language. Since children are attracted to mobile multimedia applications, it could potentially be used in learning Arabic too. Various applications have been available in the market, but most of them do not fully utilize the multimedia elements such as sounds, videos, images, and texts. In response to that, this study aims to design, develop and evaluate a mobile multimedia application. It is called A4Kids, targeted for children between 7 and 9 years old for learning Arabic language based on Cognitive Theory of Multimedia Learning CTML. First, this study initiated an investigation involving multiple fact finding techniques, which are interviews and review of related literatures to get a prototype for stakeholders’ information needs. The preliminary analysis involves interviews with expert teachers who have taught Arabic subject for more than ten years in primary schools. Then, related literatures were reviewed. Further, an application was developed, and tested involving real users. The results of user evaluation on the A4Kids indicate that it is learnable, easy to use, and useful for children. Additionally, it is capable to help them learn Arabic easily, directly, and successfully regardless of location and time.